Charmed. The final season [videorecording (DVD)] - Burge, Constance M. (Paramount : CBS DVD, 2007)
The magical Halliwell sisters - Phoebe, Piper and Paige - face their biggest challenges in love, life and death as they try one last time to fulfill their destiny. They continue their fight to protect Leo from the Angel of Death, and battle demons who conspire to take over the Underworld.